Reversal of age-associated cognitive deficits is accompanied by increased plasticity-related gene expression after chronic antidepressant administration in middle-aged mice - Li, Yan; Abdourahman, Aicha; Tamm, Joseph A.; Pehrson, Alan L.; Sánchez, Connie; Gulinello, Maria (Pharmacology, biochemistry and behavior, 2015)
Cognitive decline occurs during healthy aging, even in middle-aged subjects, via mechanisms that could include reduced stem cell proliferation, changed growth factor expression and/or reduced expression of synaptic plasticity genes. Although antidepressants alter these mechanisms in young rodents, their effects in older animals are unclear. In middle-aged mice, we examined the effects of a selective serotonin reuptake inhibitor (fluoxetine) and a multimodal antidepressant (vortioxetine) on cognitive and affective behaviors, brain stem cell proliferation, growth factor and gene expression. Twelve-month-old female C57BL/6 mice exhibited impaired visuospatial memory in the novel object placement (location) task associated with reduced expression of several plasticity-related genes. Chronic treatment with vortioxetine, but not fluoxetine, improved visuospatial memory and reduced depression-like behavior in the forced swim test in middle-aged mice. Vortioxetine, but not fluoxetine, increased hippocampal expression of several neuroplasticity-related genes in middle-aged mice (e.g., Nfkb1, Fos, Fmr1, Camk2a, Arc, Shank1, Nlgn2, and Rab3a). Neither drug reversed the age-associated decrease in stem cell proliferation. Hippocampal growth factor levels were not consistent with behavioral outcomes. Thus, a change in the expression of multiple genes involved in neuronal plasticity by antidepressant treatment was associated with improved cognitive function and a reduction in depression-like behavior in middle-aged mice. •Middle-aged mice had visuospatial memory deficits in a hippocampus-dependent task.•Middle-aged mice had lower neuroplasticity-related gene expression in the hippocampus.•Middle-aged mice had less stem cell proliferation in the hippocampus.•Vortioxetine improved visuospatial memory in middle-aged mice.•Vortioxetine increased expression of neuroplasticity-related genes in 12month old mice.